New Records of Diatoms (Bacillariales, Rhopalodiales Surirellales) with ultrastructure details from the Black Sea Coast of Turkey - Elif Yılmaz; Aydın Kaleli; Seher Dirican; Ali Özer; Hayri Dayıoğlu (Aquatic Sciences and Engineering, 2022)
Diatoms associated with the order Bacillariales, Rhopalodiales and Surirellales are well known to be presentinmarineandbrackishwaters.Inthisstudy,diatomsinthewesternBlackSeacoastsofTurkey were investigated with ultrastructure details. Species belonging to the Bacillariales, Rhopal-odiales and Surirellales were subject to light microscopy (LM) and scanning electron microscopy (SEM) analysis, and a total of twenty-four taxa were investigated. This study examines details on the morphology and biogeography of the taxa with remarks on their distribution in Turkey. The results revealed that four species were reported on the Turkish coasts for the first time. These species were Nitzschia liebethruthii, N. volvendirostrata, Epithemia guettingeri and Campylodiscus scalaris.